Izazovi "nepotpunog zakonodavstva" / Challenges of "Incomplete Legislation": Otvorena pitanja odnosa između državnog i entitetskih zakonodavstava u socijalnom osiguranju policijskih službenika na nivou Bosne i Hercegovine / open Questions of the relationship between State's and Entities' Legislations in Social Security of Police Officers at the State Level of Bosnia and Herzegovina - Mehmedović, Emir; Hadžić, Mehmed (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
The employment status of police officers in BiH is regulated by the Law on Police Officers of Bosnia and Herzegovina and the Labour Law in Institutions of Bosnia and Herzegovina, which the basic texts were adopted in 2004 with a number of amendments that followed in later years. In the context of the relationship between these two laws, the Law on Police Officers is a lex specialis in relation to the Labour Law in Institutions of BiH. Unlike the employment status of police officers of BiH, which is insufficiently but still regulated, the segment of social security of these officers, specifically social insurance, whose basic branches are pension and disability insurance, health insurance and unemployment insurance, is regulated exclusively at the entity level. Which legislation will apply in each case depends solely on the residence of the police officer. In exercising their health insurance rights, specifically the right to a salary, police officers exercise this right to varying degrees, and in certain cases with additional restrictions on exercising their rights depending on their place of residence and consequently the entity legislation applicable to them. Regarding to pension and disability insurance, which is largely harmonized at the entities level, there have been some dilemmas regarding the interpretation of the institute of retirement by some police authorities at the level of Bosnia and Herzegovina. Termination of the employement of police officers is related to the length of pensionable service. Two key questions are related to the institute of special seniority and interpretation of the institute of seniority insurance.